Paradigma Pendidikan Masyarakat Muslim Suku Bajo Wuring Kabupaten Sikka - Suryadi, Suryadi; Tinus, Agus (Jurnal Kebijakan dan Pengembangan Pendidikan, 2015)
Abstract: This research aims to find out the educational paradigm of Bajo Wiring ethnic Muslim community in SukkaDistrict. The method used in this research is descriptive qualitative. This research was conducted in SukkaDistrict in the Bajo Wiring tribe. The subject of this research is the local community. Penguin data from observations, interviews and document studies. To obtain accurate data, researchers conducted source triangulation. The results in this study indicate that there is a paradigm shift in the Bajo Muslim community who initially viewed education as not yet important to be important. Revealed various obstacles faced by the Bajo Wiring Muslim community in the world of education including the custom of the Bajo tribe involving school-age children in fishing at sea and low per capita income in the Bajo Wiring tribe as traditional fishermen resulting in their difficulties in continuing their children's education. The solution that was raised was to overcome economic problems and distance traveled Bajo elbow to the location of the school.Keywords: Education, Paradigms, Bajo Wiring tribesÂ Abstrak: Penenelitian ini bertujuan untuk mengetahui paradigma pendidikan masyarakat Muslim suku Bajo Wuring di Kabupaten Sukka. Metode yang digunakan dalam Penelitian ini adalah deskriptif kualitatif. Penelitian ini dilakukan di Kabupaten Sukka pada suku Bajo Wuring. Subjek penelitian ini adalah masyarakat setempat. Pengumh data dari hasil observasi, wawancara serta studi dokumen. Untuk memperoleh data yang akurat peneliti melakukan triangulasi sumber. Hasil dalam penelitian ini menunjukan bahwa terjadi perubahan paradigma masyarakat Muslim suku Bajo yang awalnya memandang pendidikan belum penting menjadi penting. Terungkap berbagai kendala yang di hadapi masyarakat Muslim suku Bajo Wuring dalam dunia pendidikan diantaranya adalah kebiasaan suku Bajo melibatkan anak-anak usia sekolah dalam mencari ikan dilaut serta pendapatan perkapita yang rendah dalam suku Bajo Wuring sebagai nelayan tradisional mengakibatkan sulitnya mereka dalam melanjutkan pendidikan anaknya. Solusi yang dimunculkan yakni mengatasi masalah ekonomi serta jarak tempuh permukiman siku Bajo dengan lokasi sekolah.Kata kunci: Pendidikan, Paradigma, Suku Bajo Wuring